Avaliação de saúde bucal e seu impacto na qualidade de vida da população indígena do Espírito Santo - Ramos, Deise Berger Velten (2023)
Introduction: Knowledge of the oral conditions of specific populations is essential, so that adequate planning of policies can be carried out that takes into account the real needs of these people, and studies with indigenous populations are sporadic, almost always restricted to work with small samples. The epidemiological picture of oral health among indigenous peoples in Brazil is little known due to the scarcity of scientific investigations, surveys and comprehensive censuses. Objective: To evaluate the impact caused by oral problems on quality of life, orofacial pain, tooth loss and the association with sociodemographic characteristics, need for prosthesis, use of dental services in indigenous and non-indigenous populations living in Guarani and Tupiniquin villages located in the Municipality of Aracruz, Espírito Santo. Methodology: This study was a cross-sectional observational study, in which 1084 indigenous people had their oral conditions assessed subjectively using the OHIP-14 form, through questionnaires on tooth pain and tooth loss and a visual clinical examination was also carried out to assess the condition of tooth loss. Individuals aged 20 years or older and who were residents of the Tupiniquin and Guarani villages were included. The Chi-square and/or Fisher's exact tests were used to calculate possible associations between OHIP, dental pain, tooth loss, sociodemographic conditions, use of dental services and the need for removable prostheses. Results: The prevalence of impact of oral problems on quality of life in the indigenous population was 45.7%, with individuals aged up to 50 years (OR=1.9), with a declared need for a removable partial denture (OR= 2.5) and without the need for a complete removable denture (OR=2.3) reported a greater perception of the impact of oral problems on quality of life. Tooth loss was associated with age over 51 years (OR=6.3), less education (up to 10 years of study) (OR=2.1), more impact of oral problems on quality of life (OR=2. 3). Dental pain was more common in women, aged up to 50 years, who sought dental care for urgent reasons and in those who did not require a Removable Partial Prosthesis (RPD). Conclusions: The prevalence of impact of oral problems on the quality of life of indigenous people was higher than that normally found in nonindigenous populations, as well as a more precarious situation related to dental pain and tooth loss compared to the general population. , which demonstrates the need for improvements in the planning of public policies for the prevention and promotion of oral health and also expanding access to dental services that are more effective, aiming to improve the quality of life of this vulnerable population.